(untitled) (Adzkiya : Jurnal Hukum dan Ekonomi Syariah, 2025)
This study aims to determine how much influence Islamic Corporate Social Responsibility (ICSR) which is proxied by Islamic Social Reporting (ISR), Good Corporate Governance (GCG) proxied by the Board of Independent Commissioners, Managerial Ownership and Institutional Ownership on Financial Performance. The research method used is quantitative descriptive with multiple linear regression analysis. The population of this study was 30 companies which were then taken using purposive sampling and the number of samples used was 54. The results showed that Islamic corporate social responsibility through Islamic social reporting had a significant negative effect on financial performance. The variable of good corporate governance through the Board of Independent Commissioners has a positive and insignificant effect on financial performance, for managerial ownership has a negative effect, not significant on financial performance, while institutional ownership has a significant positive effect on financial performance. Based on the results of statistical testing of Islamic Corporate Social Responsibility, the Board of Commissioners is independent, managerial ownership, and institutional ownership have a positive and significant effect on financial performance.